1999
DOI: 10.3109/10428199909145720
|View full text |Cite
|
Sign up to set email alerts
|

Development of IgG λ Multiple Myeloma in a Patient with Cutaneous CD30+Anaplastic T-cell Lymphoma

Abstract: We report a patient with an epidermotropic cutaneous T-cell lymphoma which transformed into an anaplastic cutaneous CD30+ T-cell lymphoma. Repeated relapses required prolonged systemic PUVA therapy. Two years after diagnosis, the patient had several episodes of infections of the respiratory tract. Serum electrophoresis now revealed significantly reduced polyclonal immunglobulin production and an additional band in the gamma fraction corresponding to IgG lambda monoclonal gammopathy. Thereafter, the patient suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…All the cases reported in the English language literature are described as case reports and usually associate mycosis fungoides (MF) or Sézary syndrome (SS) to a multiple myeloma (MM) or to a monoclonal gammopathy of undetermined significance (MGUS) 5–9 . To the best of our knowledge, we report the third case which associates a multiple myeloma to a cutaneous ALTCL 10,11 . Although mechanisms of this occurrence remain unclear, it seems not to be only a chance association.…”
Section: Discussionmentioning
confidence: 88%
“…All the cases reported in the English language literature are described as case reports and usually associate mycosis fungoides (MF) or Sézary syndrome (SS) to a multiple myeloma (MM) or to a monoclonal gammopathy of undetermined significance (MGUS) 5–9 . To the best of our knowledge, we report the third case which associates a multiple myeloma to a cutaneous ALTCL 10,11 . Although mechanisms of this occurrence remain unclear, it seems not to be only a chance association.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, according to various, sporadic reports, multiple myeloma is occasionally associated with other peripheral T-cell lymphoma subtypes, including cutaneous anaplastic large T-cell lymphoma, Sezary syndrome, mycosis fungoides, and primary T-cell lymphoma of the bone (Bryant et al 1982;Weiss et al 1984;Brumana et al 1993;Cartron et al 1999;Wickenhauser et al 1999;Takami and Mizunoya 2000;Gernone et al 2002;Hwang et al 2008;Tangour et al 2011). In general, the secondary myeloma occurs several years after the initial diagnosis and the subsequent treatment of the T-cell lymphoma (Bryant et al 1982;Weiss et al 1984;Brumana et al 1993;Wickenhauser et al 1999;Gernone et al 2002;Zettl et al 2002;Hwang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the secondary myeloma occurs several years after the initial diagnosis and the subsequent treatment of the T-cell lymphoma (Bryant et al 1982;Weiss et al 1984;Brumana et al 1993;Wickenhauser et al 1999;Gernone et al 2002;Zettl et al 2002;Hwang et al 2008). Various authors have suggested that the secondary neoplasms are potentially related to immunoregulatory disturbances caused by the primary lymphomas and that the malignant plasma cells may evolve from a sustained inducing stimulus provided by the neoplastic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The development of both of ALCL and MM in the same patient one after another (metachronous) has been described in 3 cases. [ 3 5 ] While the synchronous development of ALCL and MM in the same patient was reported only in one case. [ 6 ] Here we reported another one in whom ALK-negative ALCL and IgD λ-type MM were diagnosed at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of co-existence of ALCL and MM is challenging. Among above 4 patients, 1 was deceased, [ 3 ] 2 had no records about their prognosis, [ 4 , 5 ] and only one obtained complete remission. [ 6 ] In our study this patient achieved complete remission after multiple-line chemotherapies followed by autologous stem cell transplantation (ASCT).…”
Section: Introductionmentioning
confidence: 99%